Can exercise shape your brain? A review of aerobic exercise effects on cognitive function and neuro-physiological underpinning mechanisms - Ferrer-Uris, Blai; Ramos, Maria Angeles; Busquets, Albert; Angulo-Barroso, Rosa (AIMS neuroscience, 2022)
It is widely accepted that physical exercise can be used as a tool for the prevention and treatment of various diseases or disorders. In addition, in the recent years, exercise has also been successfully used to enhance people's cognition. There is a large amount of research that has supported the benefits of physical exercise on human cognition, both in children and adults. Among these studies, some have focused on the acute or transitory effects of exercise on cognition, while others have focused on the effects of regular physical exercise. However, the relation between exercise and cognition is complex and we still have limited knowledge about the moderators and mechanisms underlying this relation. Most of human studies have focused on the behavioral aspects of exercise-effects on cognition, while animal studies have deepened in its possible neuro-physiological mechanisms. Even so, thanks to advances in neuroimaging techniques, there is a growing body of evidence that provides valuable information regarding these mechanisms in the human population. This review aims to analyze the effects of regular and acute aerobic exercise on cognition. The exercise-cognition relationship will be reviewed both from the behavioral perspective and from the neurophysiological mechanisms. The effects of exercise on animals, adult humans, and infant humans will be analyzed separately. Finally, physical exercise intervention programs aiming to increase cognitive performance in scholar and workplace environments will be reviewed.